PON2 and ATP2B2 gene polymorphisms with noise-induced hearing loss - Li, Xiuting; Cao, Jinglian; Wang, Jun; Song, Haiyan; Ji, Guixiang; Dong, Qiu; Wei, Chunlong; Cao, Ying; Wang, Boshen; Zhu, Baoli; Xiao, Hang (Journal of Thoracic Disease; Vol 8, No 3 (March 18, 2016): Journal of Thoracic Disease, 2016)
Background: Noise-induced hearing loss (NIHL) is a complex disease induced by a combination of genetic and environmental factors. Paraoxonase2 (PON2) gene involved in the regulation of reactive oxygen species, and affecting the vulnerability of cochlea to NIHL, and ATPase, calcium-transporting, plasma membrane 2 (ATP2B2) gene which encodes plasma membrane calcium-transporting ATPase isoform 2 (PMCA2) are the candidate genes relating to the attack of NIHL. In this study, we investigated whether ATP2B2 and PON2 polymorphisms were associated with NIHL in Chinese of Han nationality population. Methods: We performed a case-control study between six single nucleotide polymorphisms (SNPs) (rs1719571, rs3209637 and rs4327369 within ATP2B2, rs12026, rs7785846 and rs12704796 within PON2) and NIHL in 454 subjects. All the SNPs were genotypes, using the TaqMan MGB probe assay. Odds ratios (ORs) were calculated with 95% conﬁdence intervals (95% CIs) with logistic regression analysis to test the level of association for SNPs. Results: In our study, 221 subjects with hearing loss and 233 subjects without hearing loss were recruited. The frequencies of the CG and CG + GG genotype of rs12026 (PON2) conferred risk factors for NIHL with adjusted OR values of 2.62 (95% CI, 1.69–4.06) and 2.48 (95% CI, 1.63–3.78), respectively. This kind of significance was also found at locus rs7785846, where genotypes CT and CT + TT were the risk types, with adjusted ORs of 2.52 (95% CI, 1.62–3.93) and 2.35 (95% CI, 1.54–3.58), respectively. We performed stratified analysis per noise exposure level, when it came to rs7785846 and rs12026 in the >92 dB(A) noise exposure group, the subjects who carried heterozygote were of significantly (P0.05), which may suggest that these SNPs did not have significant effects on noise susceptibility across noise exposure. Conclusions: Our research suggested that PON2 might play a role in the etiology of NIHL in Chinese of Han nationality population.